Development of qr code-assisted learning materials to improve students' numbers' abilities on spldv material in class x of ma nurul huda bercak asri cerme bondowoso: pengembangan bahan ajar - siti nur arifah, arifah; Hasanah, Nur; Ambarsari, Ida Fitriana (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2023)
This research aims to develop QR Code-assisted teaching materials to enhance students numeracy skills in the SPLDV (System of Linear Equations with Two Variables) topic for Class X students at MA Nurul Huda Bercak Asri Cerme Bondowoso. The research is an R & D (Research and Development) research or commonly known as development research, where development research is a different research from other research, because in this research we are required to develop a product that already exists so that it is suitable for use now or even in the future. The R & D research method used in this study uses the four-D or 4D model, namely: Define, Design, Develop, Disseminate. The teaching materials or modules developed in this study have been equipped with several videos that explain the material or examples of questions. In addition, the learning devices that have been developed have gone through validation tests, practicality tests and effectiveness tests. In this study, researchers used several samples of class X MA Nurul Huda Bercak Asri Cerme Bondowoso students, namely 10 people to carry out validation tests, practicality tests and effectiveness tests of learning devices. The results of the data analysis of QR code-based learning devices have met the criteria for quality and feasibility of developing learning devices that have been set, namely meeting the validity criteria with a result of 93.3%, effectiveness with a result of 86% and practicality with a result of 80%.